INFORMATION TECHNOLOGY IN LEARNING IN THE DIGITAL AGE: LITERATURE REVIEW OF THE TEACHER'S ROLE AS LEARNING FACILITATOR - Jufri, Amar; Helmy, Fatkhul; Alisyah, Siti Nur; Kurniaku, Aji; Ananda, Miftah Rizki (Proceeding International Seminar of Islamic Studies, 2023)
Education is important in forming quality human resources. Information technology (IT) has become an integral part of learning in the digital era, and can provide great benefits in improving the quality of learning. However, the use of IT in learning requires the active role of the teacher as a learning facilitator. This study aims to review the teacher's role as a learning facilitator in the implementation of IT in learning in the digital era, especially in Indonesia. Through a literature review, this study identified the teacher's role in the use of IT in learning, as well as the challenges and efforts required in implementing IT in learning. Previous research shows that the teacher's role is very important in the use of IT in learning. However, IT implementation in learning also poses challenges for teachers, such as a lack of skills in operating IT and limited access to adequate technology. Therefore, it is important for teachers to be able to choose and manage technology according to learning needs, and ensure that the use of IT in learning is in accordance with the learning objectives and educational standards set. Keywords: Education, Information Technology, Learning, Teachers, Learning Facilitators, Digital Age. as well as ensuring the use of IT in learning in accordance with the learning objectives and educational standards set. Keywords: Education, Information Technology, Learning, Teachers, Learning Facilitators, Digital Age. as well as ensuring the use of IT in learning in accordance with the learning objectives and educational standards set. Keywords: Education, Information Technology, Learning, Teachers, Learning Facilitators, Digital Age.